PENERAPAN MODEL PEMBELAJARAN COOPERATIVE TIPE INDEX CARD MATCH UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VB SEKOLAH DASAR NEGERI 121 PEKANBARU - Yusmarwati '; Zulkifli '; Hamizi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research was motivated by the low of students’ learning outcomes on the subject of Natural Sciences. It could be seen from the test results of 30 students only 46%, which totaled a minimum completeness criteria was 75. The formulation of the problem in this study was could the Cooperative learning model of Card Index Match types improve students’ learning outcomes on science subjects of VB class State Elementary School 121 Pekanbaru?. The objective of the research was to improve studens’t learning results by implementing cooperative learning model of Index Card Match type at the grade of VB students of State Elementary School 121 Pekanbaru. This study used a classroom action research conducted into two cycles with 4 stages: planning, action, observation and reflection as a basis for planning reset in the next cycle. The results obtained from this research of data analysis activities of teachers at the first encounter of the first cycle with a percentage of 62.5% (good). The second encounter of the first cycle with a percentage of 70.8% (good). The first encounter of the second cycle with a percentage of 83.3% (very good) and the second encounter of the second cycle with the percentage of 95.8% (very good). While the students’ activities of the first cycle at the first encounter with the percentage of 62.5% (good). The second encounter of the first cycle with a percentage of 66.7% (good). At the first encounter of the second cycle with a percentage of 83.3% (very good) and the second encounter of the second cycle with a percentage of 91.7% (very good). Based on these results the first daily test results in the first cycle an average of 73.2% in good categories. While in the second cycle of second daily test increased to 80.1 in good categories. From the results of this research could be concluded that the application of cooperative learning model of Index Card Match type could improve students’ learning results on natural science subject at the grade of VB State Elementary School 121 Pekanbaru.Keywords : cooperative learning of index card match type, science and learning outcomes